GC-MS-based metabolites profiling of Cosmos caudatus kunth leaves possessing alpha-glucosidase inhibitory activity - Javadi, Neda (2014)
A large number of plant metabolites have provided as an incomparable chemical source for drug development. Cosmos caudatus, which is known as Ulam raja, is one of the herbal plants used in Malaysia. This plant has been used traditionally to enhance vitality. The current study focused on the evaluation of the α-glucosidase inhibitory activity of different ethanolic extracts of Cosmos caudatus (C. caudatus). Six series of extracted samples including water, 20%, 40%, 60%, 80%, and 100% ethanol (EtOH) were utilized. The IC50 values for these six series of extracts from 13.7 to 298 µg/mL. The highest α-glucosidase inhibitory activity was obtained from EtOH extract which was comparable to quercetin and more potent than acarbose. In contrast, water extract exhibited the lowest activity. To identify and profile the chemical compositions of the samples, gas chromatography-mass spectrometry (GC-MS) was employed. GC-MS combined with orthogonal partial least-squares analysis (OPLS) was applied to detect antidiabetic activity of C. caudatus. The OPLS showed an obvious and remarkable separation into six clusters representing the six different ethanolic extracts. Therefore, GC-MS was possible to be combined with MVDA for identification of compounds that inhibited α-glucosidase activity. Catechin, α-linolenic acid, α-d-glucopyranoside and vitamin E were identified and indicate the potential antidiabetic activity of this herb. In the second part of this study, C. caudatus samples were subjected to seven different storage times (0, 2, 4, 6, 8, 10 and 12 h) at room temperature before extraction and α-glucosidase inhibitory activity were determined for the respective samples. The IC50 values ranged from 12.6 to 40.9 µg/mL. α-Glucosidase inhibitory activity for the first group (fresh) was the highest with an IC50 value of 12.6 µg/mL, which was better than that of quercetin. After 12 h of storage, the extract exhibited the lowest activity with an IC50 value of 40.9 µg/mL, which is still better than that of acarbose. As a model experiment, GC-MS of the extracts obtained from the Ulam raja was correlated with the α-glucosidase inhibition activity with OPLS analysis to determine the antidiabetic compounds. A profound chemical change in the primary and secondary metabolites was observed. In the first group, catechin, α-tocopherol (vitamin E), benzoic acid, cyclohexen-1-carboxylic acid, myo-inositol, stigmasterol, and lycopene were observed. High quantities of primary metabolites including sugars, such as sucrose, α-d-galactopyranose and turanose were observed in samples stored for a long period of time (12 h). This study may provide guidance in the determination of pharmacological mechanism as well as the development of medicinal preparations, nutraceuticals or functional foods from C. caudatus for diabetes and related symptoms.